Fifteen new species of Chilicola (Hymenoptera: Apoidea; Colletidae) - Packer, Laurence; Genaro, Julio A. (Zootaxa, 2007)
Fifteen new species of the xeromelissine bee genus Chilicola are described. Most are either outliers not obviously belonging to currently known subgenera or expand our concepts of previously described subgenera. Species that do not readily fall into presently recognized subgenera are: Chilicola obesifrons Packer, n. sp. and the closely related C. catamarcense Packer, n. sp.; C. unicarinata Packer, n. sp. and the closely related C. chubutense Packer, n. sp., and three comparatively isolated species: C. biguttata Packer, n. sp., C. tregualemu Packer, n. sp., and C. setosicornis Packer, n. sp.. Species that fall within previously described subgenera are: C. (Chilioediscelis) aenigma Packer, n. sp., C. (Prosopoides) granulosa Packer, n. sp., C. (Pseudiscelis) nanula Packer, n. sp., C. (Stenoediscelis) denisii Packer, n. sp., C. tricarinata Packer, n. sp., C. tricarinatoides Packer, n. sp., and C. clavillo Packer, n. sp. The last three species belong to “Oedis- celisca”, a subgenus subsumed within Oediscelis by Michener (1995) but requiring re-evaluation. Chilicola nanula and C. aenigma expand the scope of their respective subgenera. A fifteenth species, C. liliana Packer, n. sp., is not placed to subgenus due to a lack of males. Toro and Moldenke’s (1979) subgenus Stenoediscelis is returned from synonymy and new characters justifying this resurrection are provided.